Brucella microti‐like prevalence in French farms producing frogs. Issue 2 (21st October 2019) - Jaÿ, Maryne; Freddi, Luca; Mick, Virginie; Durand, Benoit; Girault, Guillaume; Perrot, Ludivine; Taunay, Benoit; Vuilmet, Thomas; Azam, Didier; Ponsart, Claire; Zanella, Gina
Abstract: In the last 10 years, many atypical novel members of Brucella species have been reported, including several Brucella inopinata ‐like strains in wild‐caught and "exotic" amphibians from various continents. In 2017, a strain of Brucella was isolated for the first time in animals from a French farm producing frogs— Pelophylax ridibundus —for human consumption and identified as B. microti ‐like. Following this first isolation, investigations were performed in this farm as well as in the farm of the research unit that provided the domestic frog strain to estimate the prevalence of B. microti ‐like infection and its presence in the surrounding environment. Farming practices were investigated and samples including frogs at different development stages, surface tank swabs, water, feed and soil were analysed by real‐time PCR and bacteriological methods. High B. microti ‐like prevalence values (higher than 90%) were obtained in frog samples in the commercial farm, and its presence was highlighted in the environmental samples except feed. In the research unit farm, B. microti ‐like species was also isolated and detected in frog and environmental samples. These results show that B. microti ‐like organisms are able to colonize amphibians and persist in their environment. Its presence could constitute a possible risk for consumers and workers proving the importance of assessing the zoonotic and pathogenic potentials of these new and atypical Brucella species.